Pore Pressure and Compartmentalization of Carbonate Reservoirs in Northern Madura Platform - East Java Basin, Indonesia - Ecep Suryana; Lambok M. Hutasoit; Agus M. Ramdhan; Dwiharso Nugroho; Arifin Arifin (Indonesian Journal on Geoscience, 2023)
Understanding pore pressure characteristics in carbonate reservoirs is essential, because it concerns all aspects of subsurface, drilling, and occupational safety, as well as the environment in oil and gas exploration and exploitation. In this study, the pore pressure regime and connectivity of the carbonate reservoir (compartmentalization) of Kujung and Ngimbang Formations in the northern Madura Platform of East Java Basin are characterized by utilizing direct pressure data and wireline logs from five wells. The result shows that both hydrostatic and slight overpressure conditions are found in these formations, further indicating the presence of carbonate compartmentalization. The magnitudes of overpressure, however, are mostly very low, with an average of ~37 psi. Four compartmentalized carbonates are identified based on the presence of different pressure gradients in the water leg. The slight overpressure in the carbonates is likely owing to pressure transference from overpressured shale at depth. In addition, by using acoustic impedance from seismic, the depositional environments of the carbonates are interpreted as lagoon and tidal flat. These environments support the occurrence of patch reef carbonate buildups in the Kujung and Ngimbang Formations, which later become a good environment for overpressure generation and carbonate reservoir compartmentalization. Keywords: carbonates, compartmentalization, depositional environment, slight overpressure